Assessment of 'Fitting to Outcomes Expert' FOX™ with new cochlear implant users in a multi-centre study. (March 2015) - Battmer, Rolf-Dieter; Borel, Stephanie; Brendel, Martina; Buchner, Andreas; Cooper, Huw; Fielden, Claire; Gazibegovic, Dzemal; Goetze, Romy; Govaerts, Paul; Kelleher, Katherine; Lenartz, Thomas; Mosnier, Isabelle; et al.
Abstract : Objective: To compare the fitting time requirements and the efficiency in achieving improvements in speech perception during the first 6 months after initial stimulation of computer-assisted fitting with the Fitting to Outcome eXpert' (FOX) and a standard clinical fitting procedure. Method: Twenty-seven post-lingually deafened adults, newly implanted recipients of the Advanced Bionics HiRes 90K™ cochlear implant from Germany, the UK, and France took part in a controlled, randomized, clinical study. Speech perception was measured for all participants and fitting times were compared across groups programmed using FOX and conventional programming methods. Results: The fitting time for FOX was significantly reduced at 14 days ( P  < 0.001) but equivalent over the 6-month period. The groups were not well matched for duration of deafness; therefore, speech perception could not be compared across groups. Discussion: Despite including more objective measures of performance than a standard fitting approach and the adjustment of a greater range of parameters during initial fitting, FOX did not add to the overall fitting time when compared to the conventional approach. FOX significantly reduced the fitting time in the first 2 weeks and by providing a standard fitting protocol, reduced variability across centres. Conclusions: FOX computer-assisted fitting can be successfully used at switch on, in different clinical environments, reducing fitting time in the first 2 weeks and is efficient at providing a usable program.